1998
DOI: 10.1002/(sici)1521-4141(199803)28:03<855::aid-immu855>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of stem cell factor and granulocyte colony-stimulating factor enhances the growth of human progenitor B cells supported by murine stromal cell line MS-5

Abstract: We have developed a long-term culture system using the murine bone marrow stromal cells MS-5 to support the growth of progenitor B cells with CD34-, CD10 + , CD19 + , and cyto-plasmic ? chain (C ?)-negative surface phenotype from human CD34 + cells purified from umbilical cord blood (CB). When 10 3 CB CD34 + cells/well were seeded on MS-5 stromal cells at the beginning of culture in the absence of exogenously added cytokines, progenitor B cells first appeared after 14 days, and the maximal cell production was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
(33 reference statements)
8
46
0
Order By: Relevance
“…Human CB CD34 ϩ CD38 Ϫ cells were cultured with MS-5 cells in ␣-MEM medium containing 10% FCS, 100 ng/ml recombinant human SCF, and 10 ng/ml recombinant human G-CSF (34). They were directly sorted into wells of 96-well flat-bottom plates preseeded with MS-5 cells, and then cultured for 6 wk.…”
Section: Coculture Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Human CB CD34 ϩ CD38 Ϫ cells were cultured with MS-5 cells in ␣-MEM medium containing 10% FCS, 100 ng/ml recombinant human SCF, and 10 ng/ml recombinant human G-CSF (34). They were directly sorted into wells of 96-well flat-bottom plates preseeded with MS-5 cells, and then cultured for 6 wk.…”
Section: Coculture Assaymentioning
confidence: 99%
“…Fortunately, the murine MS-5 stromal cell clone used in the experiments previously described also supports formation of human B lineage lymphocytes in culture (34). The hematopoietic stem cell-enriched CD34 ϩ CD38 Ϫ fraction was isolated from umbilical CB, and two cell concentrations were used to initiate cocultures on MS-5 monolayers (Table I).…”
Section: Adiponectin Inhibits B Lymphopoiesis Only When Stromal Cellsmentioning
confidence: 99%
“…Campana and colleagues developed an assay system by employing co-culture with human bone marrow-derived stromal cells, which provided reproducible growth of leukemic B-precursor cells from children with ALL. [22][23][24] Nishihara et al 25 recently reported a similar but xenogenic co-culture system for normal pro-B cells with the mouse bone marrow-derived stroma cell line MS-5. We co-cultured ALL blasts with MS-5 to develop an assay system that allows easy quantitative assessment of ALL cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…MS-5 is one such cell line, derived from noninfected Dexter-type murine long-term marrow culture, which supports CFU-S maintenance 21 and acts synergistically with human growth factors to stimulate the formation of blast colonies and macroscopic colonies from CD34 + CD38 Ϫ primitive progenitors in short-term methylcellulose assays. 22 MS-5, alone 23 or in combination with SCF and G-CSF, 24,25 also supports the proliferation of primitive lymphohematopoietic progenitors that are capable of differentiation along both myeloerythroid and lymphoid lineages and their differentiation toward the B cell lineage. Furthermore, a recent study has demonstrated that, in the presence of multiple cytokines, MS-5 cells promote a net increase of LTC-IC through self-renewal divisions.…”
mentioning
confidence: 87%